Regulator of calcineurin 1 modulates vascular contractility and stiffness through the upregulation of COX-2-derived prostanoids - García Redondo, Ana B.; Esteban, Vanesa; Briones, Ana M.; Díaz del Campo, Lucía S.; González Amor, María; Méndez Barbero, Nerea; Campanero, Miguel R.; Redondo, Juan M.; Salaices, Mercedes (Elsevier, 2018)
Cyclooxygenase-2 (COX-2) derived-prostanoids participate in the altered vascular function and mechanical properties in cardiovascular diseases. We investigated whether regulator of calcineurin 1 (Rcan1) participates in vascular contractility and stiffness through the regulation of COX-2. For this, wild type (Rcan1+/+) and Rcan1-deficient (Rcan1¿/¿) mice untreated or treated with the COX-2 inhibitor rofecoxib were used. Vascular function and structure were analysed by myography. COX-2 and phospo-p65 expression were studied by western blotting and immunohistochemistry and TXA2 production by ELISA. We found that Rcan1 deficiency increases COX-2 and IL-6 expression and NF-¿B activation in arteries and vascular smooth muscle cells (VSMC). Adenoviral-mediated re-expression of Rcan1.4 in Rcan1¿/¿ VSMC normalized COX-2 expression. Phenylephrine-induced vasoconstrictor responses were greater in aorta from Rcan1¿/¿ compared to Rcan1+/+ mice. This increased response were diminished by etoricoxib, furegrelate, SQ 29548, cyclosporine A and parthenolide, inhibitors of COX-2, TXA2 synthase, TP receptors, calcineurin and NF-¿B, respectively. Endothelial removal and NOS inhibition increased phenylephrine responses only in Rcan1+/+ mice. TXA2 levels were greater in Rcan1¿/¿ mice. In small mesenteric arteries, vascular function and structure were similar in both groups of mice; however, vessels from Rcan1¿/¿ mice displayed an increase in vascular stiffness that was diminished by rofecoxib. In conclusion, our results suggest that Rcan1 might act as endogenous negative modulator of COX-2 expression and activity by inhibiting calcineurin and NF-kB pathways to maintain normal contractility and vascular stiffness in aorta and small mesenteric arteries, respectively. Our results uncover a new role for Rcan1 in vascular contractility and mechanical properties.